Multifaceted Roles of Melatonin in Sleep Disorders - Dunya Talib; Rana (Wasit Journal for Pure Sciences, 2024)
Hormone protein melatonin helps regulate the sleep–wake cycle or circadian rhythm, making it a critical substance in sleep regulation. Melatonin synthesis mainly occurs in the epiphysis of the pineal gland, although extra-pineal melatonin has been observed in other sites of the body, such as salivary glands, the gastrointestinal tract, the placenta and breast milk. Over the years, research into melatonin has shown that it has multiple roles in sleep disorders, revealing its mechanisms of action, clinical implications and therapeutic performance. In this paper, we review recent findings on the role of melatonin in sleep disorders which include insomnia, delayed sleep phase disorder (DSPD), jet lag, and shift work sleep disorder (SWSD). In addition, we report results where melatonin agonists and novel therapeutic targets have been designed and utilized to manipulate the melatonin receptors. This paper helps delineate melatonin’s role in sleep disorders from the literature, and clarify new perspectives for prevention and treatment of human health.